Managing Water Quality in the Face of Uncertainty A Robust Decision Making Demonstration for EPA's National Water Program - Fischbach, Jordan R. (RAND Corporation, 2015)
The U.S. Environmental Protection Agency and its partners develop implementation plans to meet water quality standards. Climate change and other key drivers may significantly affect these plans, but are often neglected due to uncertainty. This study uses two case studies to demonstrate how Robust Decision Making (RDM) can help to address future uncertainty by identifying vulnerabilities in water quality plans and suggesting appropriate responses.